The Meaning of Islamic Mindfulness-Based Counseling Experience for Students with Anxiety Problems - Syafii, Muhammad Hisyam (UIN Fatmawati Sukarno Bengkulu, 2024)
This study aims to explore the meaning of the Islamic Mindfulness-Based Counseling (IMBC) experience for students with anxiety problems. Using a qualitative systematic literature review approach, this research analyzes relevant studies published between 2020 and 2024. The findings indicate that integrating mindfulness principles with Islamic values—such as muraqabah (self-monitoring), muhasabah (self-reflection), and khusyu' (spiritual focus)—offers a more holistic approach to anxiety management. Students undergoing IMBC report increased self-awareness, spiritual well-being, and cognitive reappraisal of anxiety as a test of faith rather than a mere psychological disorder. Moreover, techniques such as mindful prayer, dhikr, and Qur'anic reflection contribute significantly to emotional regulation and psychological resilience. These findings highlight the potential of IMBC as a culturally and religiously relevant intervention for Muslim students. Future research should employ experimental methods to measure IMBC's effectiveness quantitatively and explore its impact on broader psychological constructs.